Amidinato germylene-zinc complexes: synthesis, bonding, and reactivity - Yadav, Sandeep; Kumar, Rohit; Raj, K. Vipin; Yadav, Prashant; Vanka, Kumar; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
Despite the explosive growth of germylene compounds as ligands in transition metal complexes, there is a modicum of precedence for the germylene zinc complexes. In this work, the synthesis and characterization of new germylene zinc complexes [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> ZnX2](2)(X= Br (2) and I (3)) supported by (benz)-amidinato germylene ligands are reported. The solid-state structures of2and3have been validated by single-crystal X-ray diffraction studies, which revealed the dimeric nature of the complexes, with distorted tetrahedral geometries around the Ge and Zn center. DFT calculations reveal that the Ge-Zn bonds in2and3are dative in nature. The reaction of2with elemental sulfur resulted in the first structurally characterized germathione stabilized ZnBr(2)complexes PhC(NtBu)(2)Ge(=S){N(SiMe3)(2)}-> ZnBr2(5). Therefore, the Ge=S in5is in-between Ge-S single and Ge=S double bond length, owing to the coordination of a sulfur lone pair of electrons to ZnBr2.
Keywords: DFT; Germathione; Germylene; X-ray Structure; zinc

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Deoxygenative hydroboration of primary and secondary amides: a catalyst-free and solvent-free approach - Kumar, Rohit; Bisai, Milan Kumar; Jain, Shailja; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
In contrast to the recent reports on catalytic hydroboration of amides to amines with pinacolborane (HBpin), a simple catalyst-free and solvent-free method for the hydroboration of a variety of amides has been realized. To get the mechanistic insights, DFT calculations have been performed.

Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands

Hydroformylation of olefins by metals other than rhodium - Kumar, Rohit; Chikkali, Samir H. (Journal of Organometallic Chemistry, 2022)
Metal catalyzed hydroformylation of alkenes is an atom economic transformation to construct useful aldehydes and is being industrially practiced for decades. The most commonly used metal for this transformation on an industrial scale is rhodium. However, rhodium is rare, costly, and is depleting at a skyrocketing rate. Therefore, finding a suitable alternative to rhodium for metal-catalyzed hydroformylation has been on the radar of many academic and industrial researchers. This review presents the scientific advancements reported in the hydroformylation reaction using metals other than rhodium. An overview of recent progress in palladium, iridium, ruthenium, cobalt, platinum, and iron-catalyzed hydroformylation is presented. Hydroformylation of alkenes and alkynes, using syngas as well as syngas surrogates is examined. The evaluation of the current status of non-rhodium metals in hydroformylation suggests that the field is still in a nascent stage and, except cobalt, no other metal poses a significant challenge to the dominance of rhodium. Deep mechanistic understanding of rate-limiting elementary steps in the non-rhodium metals is largely missing and thus only limited success is reported. Intense research on ligand design, mechanistic understanding, and choice of non-rhodium metal precursors may change this scenario in near future.
Keywords: aldehydes; alkenes; catalysis; Hydroformylation; Non-rhodium metals

Luminescent magnesium complexes with intra- and inter-ligand charge transfer - Kumar, Rohit; Pahar, Sanjukta; Chatterjee, Joy; Dash, Soumya Ranjan; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we report two 2,2'-pyridylpyrrolide (PyPyrH) ligand supported magnesium complexes (1 and 2), which demonstrate bright luminescence with a quantum yield of 22% and 14% in the solid state, respectively. Theoretical calculations reveal that their emissive properties originate from the intra- and inter-ligand charge transfer.

Mechanistically guided one pot synthesis of phosphine-phosphite and its implication in asymmetric hydrogenation - Sen, Anirban; Kumar, Rohit; Pandey, Swechchha; Raj, K. Vipin; Kumar, Pawan; Vanka, Kumar; Chikkali, Samir H. (European Journal of Organic Chemistry, 2022)
Although hybrid bidentate ligands are known to yield highly enantioselective products in asymmetric hydrogenation (AH), synthesis of these ligands is an arduous process. Herein, a one pot, atom-economic synthesis of a hybrid phosphine-phosphite (L1) is reported. After understanding the reactivity difference between an 0-nucleophile versus C-nucleophile, one pot synthesis of Senphos (L1) was achieved (72%). When L1 was treated with [Rh], P-31 NMR revealed bidentate coordination to Rh. Senphos, in the presence of rhodium, catalyzes the AH of Methyl-2-acetamido-3-phenylacrylate and discloses an unprecedented turn over frequency of 2289, along with excellent enantio-selectivity (92%). The generality is demonstrated by hydrogenating an array of alkenes. The AH operates under mild conditions of 1-2 bar H-2 pressure, at room temperature. The practical relevance of Ll is demonstrated by scaling-up the reaction to 1 g and by synthesizing DOPA, a drug widely employed for the treatment of Parkinson's disease. Computational insights indicate that the R isomer is preferred by 3.8 kcal/mol over the S isomer.
Keywords: asymmetric hydrogenation; catalysis; DOPA synthesis; One pot synthesis; Phosphine-phosphite ligand

Monomeric magnesium catalyzed alkene and alkyne hydroboration - Kumar, Rohit; Dutta, Sayan; Sharma, Vishal; Singh, Praval P.; Gonnade, Rajesh G.; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2022)
In this work, two monomeric magnesium alkyl complexes (1 and 2) were prepared using bis(phosphino)carbazole framework and among them 1 has been used as a catalyst for hydroboration of alkenes and alkynes with pinacolborane (HBpin). A broad variety of aromatic and aliphatic alkenes and alkynes were efficiently reduced. Anti-Markovnikov regioselective hydroboration of alkenes and alkynes was achieved, which was confirmed by deuterium-labelling experiments. The work represents the first example of the use of magnesium in homogeneous catalytic hydroboration of alkene with broad substrate scope. Experimental mechanistic investigations and DFT calculations provided insights into the reaction mechanism. Finally, the hydroboration protocol was extended to terpenes.
Keywords: carbazole; Magnesium; monomeric complexes; phosphorous; X-ray Structure

Well-defined calcium compound catalyzes trimerization of arylisocyanates into 1,3,5-triarylisocyanurates - Kumar, Rohit; Sharma, Vishal; Jain, Shailja; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (ChemCatChem, 2022)
We report the synthesis of a calcium complex (2) bearing a tetradentate monoanionic ligand with a diaminoethane core and phenolate and pyridine peripheral donors. Single crystal X-ray studies on 2 revealed that LiI was also co-crystallized, leading to a four-membered ring with four different elements. 2 was found to be an efficient catalyst for the cyclotrimerization of a variety of aromatic isocyanates under mild conditions.
Keywords: calcium; Cyclotrimerization; Isocyanurates; Tetradentate ligand

Controlled reduction of isocyanates to formamides using monomeric magnesium - Kumar, Rohit; Sharma, Vishal; Banerjee, Subhrashis; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2023)
This work describes a transition metal-free methodology involving an efficient and controlled reduction of isocyanates to only formamide derivatives using pinacolborane (HBpin) as the hydrogenating agent and a bis(phosphino)carbazole ligand stabilized magnesium methyl complex (1) as the catalyst. A large number of substrates undergo selective hydroboration and give exclusively N-boryl formamides.

Iron-catalysed highly selective hydroalkoxycarbonylation of alkynes using CO as C1 source - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (Catalysis Science & Technology, 2023)
Though precious and rare, late-transition metals have been extensively used in metal-catalysed carbonylation reactions in organic transformations. On the other hand, base metals are abundant and cheap, but their practical utilization in carbonylation reactions is rarely explored. Here, we report iron-catalysed hydroalkoxycarbonylation of alkynes to alpha,beta-unsaturated esters in one pot. A readily available iron precursor [Fe2(CO)9] in the presence of a diimine ligand L7 catalyzes the conversion of alkynes to alpha,beta-unsaturated esters under 10 bar CO pressure. This operationally simple protocol tolerates various functional groups and allows facile access to about 40 alpha,beta-unsaturated esters. The synthetic utility of the reaction has been demonstrated by scaling up the reaction to 1 g and by preparing sunscreen/antifungal agents. The kinetic study suggests that the reaction is an approximate 1st order with respect to the iron catalyst, and the initial rate of the reaction is 3.6 x 10-2 M h-1. Mechanistic investigations using NMR spectroscopy indicated the existence of an [Fe-H] intermediate, and control experiments using a radical trapping reagent and EPR revealed the absence of any radical species in the reaction. Precious and rare, late transition metals have been extensively used in carbonylation. An earth abundant iron-catalyst is reported here for hydroalkoxycarbonylation of alkynes in the presence of CO as C1 source.

Iron-catalyzed alkoxylation, dehydrogenative-polymerization and tandem hydrosilylative-alkoxylation - Sen, Anirban; Kumar, Rohit; Tewari, Tanuja; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry- a european journal, 2023)
Alkoxylation, hydrosilylative-alkoxylation, and dehydrogenative-polymerization are some of the most widely used transformations in synthetic chemistry. However, these transformations are traditionally catalyzed by precious, and rare late-transition metals. Presented here is a molecularly defined iron complex that catalyzes alkoxylation, tandem hydrosilylative-alkoxylation, and dehydrogenative polymerization of silanes under mild conditions. The iron complex [Fe(CO)(4)(H)(SiPh3)] 1 catalyzes a direct Si-O coupling reaction between an array of silanes and alcohols to produce desired alkoxysilanes in excellent yield, with H-2 as the only byproduct. The iron catalyst tolerates various functional groups and provides access to 20 alkoxysilanes, including essential molecules such as & beta;-citronellol and cholesterol. Further, complex 1 catalyzes the polymerization of renewable diol and silane monomer to produce a renewable and degradable poly(isosorbide-silyl ether). Remarkably, complex 1 catalyzes a tandem hydrosilylative-alkoxylation of alkynes under mild conditions to yield unsaturated silyl ethers. The synthetic utility has been demonstrated by gram-scale alkoxylation and hydrosilylative-alkoxylation reactions.
Keywords: alkoxylation; dehydrogenative polymerization; earth abundant catalysts; hydrosilylative-alkoxylation; Iron Catalyst

Iron-catalyzed magnesium-mediated formal hydroformylation of alkynes and alkenes - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (ChemCatChem, 2023)
Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is iron-catalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces alpha,beta-unsaturated aldehydes in good to excellent conversion. Mechanistic investigations revealed the presence of vinyl magnesium intermediate, the kinetic study disclosed the first-order dependence of the reaction on iron loading, and the control experiment authenticated the iron catalyst's homogeneous nature. The scope of this methodology was amplified, and 20 alkenes were examined. [Fe(acac)(3)] in the presence of ligand, alkyl magnesium halide, and dimethyl formamide catalyzed the hydroformylation of alkenes and displayed good to excellent conversion. An earth-abundant iron catalyst offering a syngas cylinder-free safe alternative to high-pressure hydroformylation has been reported.
Keywords: aldehydes; alkenes; Alkynes; Hydroformylation; iron catalysis

Rh-catalyzed asymmetric hydroformylation of olefins using phosphorus ligands - Kumar, Rohit; Sen, Anirban; Chikkali, Samir H. (Journal of chemical sciences, 2023)
Easily accessible BINOL-based monodentate phosphite ligand L1 and hybrid ligand L2 have been synthesized in good yield by following a one-pot, two-step protocol. A single 31P resonance at 146.6 ppm confirmed the formation of L1. Subsequent 1-2D NMR and mass spectrometric analysis authenticated the existence of L1. These ligands afforded excellent activity and regio-selectivity in the Rh-catalyzed AHF of styrenic substrates. L1 showed excellent regioselectivity but did not discriminate between the two enantiomers, while L2 displayed an enantiomeric excess (ee) of up to 20%. In our attempts to understand the reasons for low ee, the coordination behavior of L2 was investigated. The coordination study revealed that L2 coordinates with the Rh as a monodentate ligand, although there are two P-sites. It was found that only the phosphine arm was coordinated to the Rh and the phosphite arm stayed away from the Rh core at the ambient temperature, leading to moderate ee.Graphical abstractOne-step synthesis of a phosphite (L1) and a phosphine-phosphite (L2) ligand and their implication in the asymmetric hydroformylation of olefins with excellent regioselectivity (>95%) and moderate enantioselectivity (up to 20%) is reported.
Keywords: catalysis; coordination; Hydroformylation; Phosphine-phosphite ligand; Phosphite ligand

Iron in organometallic transformations: a sustainable substitute for noble metals - Kumar, Rohit; Tewari, Tanuja; Chikkali, Samir H. (ChemCatChem, 2024)
Transition metal catalysis plays a pivotal role in chemical synthesis. Noble metals often grab significant attention in organometallic catalysis due to their high reactivity. However, the serious issues associated with these metals such as low abundance, toxicity, geopolitical limitations, and volatile prices are driving the scientific community to discover sustainable alternatives. In this context, iron appears to be the first choice as an alternative metal due to its unique properties, including a range of stable oxidation states, Lewis acidity, high abundance in the earth's crust, and low toxicity. Over the past two decades, substantial progress has been made in iron catalysis. This overview examines the recent developments in iron-catalyzed industrially relevant transformations such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. As witnessed throughout this review, the performance of iron can be significantly altered by suitable ligand selection and by tailoring the electronic and steric properties of the iron center. While noble metals remain the industry work-horse, iron is inching closer and with extensive scientific understanding, it may replace noble metals in the near future. Late transition metals catalyze several reactions and have been the industry work-horse for decades. While, earth abundant metals are rarely used in industrially relevant transformations. In this overview, we examine the recent development in iron-catalyzed industrially relevant reactions such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. Iron is inching closer and may replace noble metals in near future. image
Keywords: Alkene Isomerization; alkyne; Carbonylation; depolymerization; Hydrophosphination; Hydrosilylation; iron catalysis

Iron-catalyzed (E)-selective hydrosilylation of alkynes: scope and mechanistic insights - Sen, Anirban; Tewari, Tanuja; Kumar, Rohit; Vinod, C. P.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Catalysis Science and Technology, 2024)
Iron-catalyzed hydrosilylation of internal alkynes has been rarely reported. Even in these rare cases, additives have been used for the success of the reaction, which often creates a problem for the functional group tolerance of the reaction. Herein, we report an additive-free iron-catalyzed (E)-selective hydrosilylation of internal alkynes in the presence of a phosphine ligand. A low-valent Fe(0) complex [Fe(CO)(3)(BDA)] {[Fe-1]} catalyzed the hydrosilylation of alkynes at 60 to 120 degrees C, exhibited a broad substrate (24 substrates) scope and tolerated different functional groups. The synthetic utility of the reaction was demonstrated by a gram scale experiment, preparing alkenes, and by chemo-selective hydrosilylation. The modus operandi of the reaction has been investigated by i) homogeneity test, ii) radical trapping experiments, iii) X-ray photoelectron spectroscopy, and iv) by preparing a Fe(II) complex as catalyst control. These mechanistic investigations revealed a two-electron pathway for the hydrosilylation of alkynes. In addition, kinetic investigations were undertaken to shed light on the rates of the reaction. Kinetic studies suggest the absence of an induction period, and the reaction is first order with respect to the concentration of iron catalyst [Fe-1] and zeroth order with respect to the substrate (alkyne). The Hammett plot suggests that strongly electron-withdrawing groups on the alkyne favour the hydrosilylation reaction. Meanwhile Eyring analysis suggests that the rate-determining step likely involves an associative pathway. Based on the findings of the mechanistic and kinetic investigation, a plausible Chalk-Harrod-type mechanism is likely to be operative. The proposed mechanism is substantiated by computational investigations, which suggested that the Chalk-Harrod mechanism is kinetically more favored by 15.8 kcal mol(-1) over the modified Chalk-Harrod mechanism.

Lanthanide mimicking by magnesium for oxazolidinone synthesis - Kumar, Rohit; Mahata, Biplab; Gayathridevi, S.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Chemistry- a european journal, 2024)
In the last decade, magnesium complexes have emerged as a viable alternative to transition-metal catalysts for the hydrofunctionalization of unsaturated bonds. However, their potential for advanced catalytic reactions has not been thoroughly investigated. To address this gap, we have developed a novel magnesium amide compound (3) using a PNP framework that is both bulky and flexible. Our research demonstrates that compound 3 can effectively catalyze the synthesis of biologically significant oxazolidinone derivatives. This synthesis involves a tandem reaction of hydroalkoxylation and cyclohydroamination of isocyanate using propargyl alcohol. Furthermore, we conducted comprehensive theoretical calculations to gain insights into the reaction mechanism. It is important to note that these types of transformations have not been reported for magnesium and would significantly enhance the catalytic portfolio of the 7th most abundant element. A monomeric magnesium compound was employed as a catalyst for the cascade cyclization of propargylic alcohol and isocyanate, resulting in the formation of pharmaceutically significant oxazolidinone derivatives. This transformation, previously attributed solely to transition metals or lanthanides, signifies a noteworthy advancement.image
Keywords: catalysis; Magnesium; oxazolidinone; pincer ligand; Sustainability

Integrated flue gas CO2 capture and conversion to formate: a sustainable approach - Kumar, Rohit; Majumder, Supriyo; Singh, Chadrodai Pratap; Samanta, Chanchal; Newalkar, Bharat L.; Krishnamurty, Sailaja; Das, Raj Kumar (ChemSusChem, 2025)
Industrial CO2 emissions, characterized by dilute streams and impurity complexity, demand energy-efficient mitigation strategies beyond conventional capture technologies. Here, an integrated CO2 capture and conversion (ICCC) system is reported employing a heterogenized iridium catalyst-hydroxyquinoline-ligated Cp*Ir-Cl immobilized on amine-functionalized silica-that directly converts CO2 from synthetic flue gas containing SOx, NOx, and O2 to formate with 100% selectivity. The catalyst delivers remarkable activity, achieving turnover numbers up to 10,286 within 16 h. Density functional theory reveals that its square pyramidal geometry, induced by the hydroxyquinoline ligand, enhances Ir-N(ring) bond strength and electronic delocalization, thereby improving hydration energy, structural robustness, and catalytic efficiency. Importantly, the catalyst system demonstrates excellent durability, maintaining full activity over five regeneration cycles. Hydrogenation in a 1 M DABCO medium, followed by thermal decomposition of the amine-formate adduct at 150 degrees C, enables efficient lean amine regeneration, allowing subsequent flue gas capture and formate production without performance loss. This closed-loop strategy delivers a sustainable, contaminant-tolerant, and recyclable CO2-to-formate platform with strong promise for scalable industrial deployment.
Keywords: CO2 capture; flue gases; integrated capture and conversions; net zero future; Recycle